2020
DOI: 10.1158/1078-0432.ccr-19-3972
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Omics Analysis Reveals Soluble Cadherin-3 as a Survival Predictor and an Early Monitoring Marker of EGFR Tyrosine Kinase Inhibitor Therapy in Lung Cancer

Abstract: Introduction: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) benefit advanced lung adenocarcinoma (ADC) patients harboring activating EGFR mutations. We aimed to identify biomarkers to monitor and predict the progression of patients receiving EGFR-TKIs via a comprehensive omic analysis. Methods:We applied quantitative proteomics to generate the TKI resistance-associated pleural effusion (PE) proteome from ADC patients with or without EGFR-TKI resistance. Candidates were selected from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In our study, it was also found to be overexpressed in EGFR-MT LUAD. Hsiao et al (2020b) found that CDH3 overexpression is related to the patients’ EGFR-TKI resistance, and reducing the expression level of CDH3 can increase the sensitivity of EGFR-TKI in patients. Moreover, sCDH3 was positively associated with the tumor stage in non–small-cell lung cancer, although it has not been found to have a significant effect on the prognosis in our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, it was also found to be overexpressed in EGFR-MT LUAD. Hsiao et al (2020b) found that CDH3 overexpression is related to the patients’ EGFR-TKI resistance, and reducing the expression level of CDH3 can increase the sensitivity of EGFR-TKI in patients. Moreover, sCDH3 was positively associated with the tumor stage in non–small-cell lung cancer, although it has not been found to have a significant effect on the prognosis in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Although the other 5 hub genes in our study did not suggest significance for the OS of EGFR-MT LUAD patients, studies have confirmed that they are closely related to EGFR-MT LUAD metastasis, recurrence, and drug resistance. Ting et al found that high CDH3 expression is related to EGFR-TKI resistance ( Hsiao et al, 2020a ); Cao et al found that high CST1 expression can be used as a marker for recurrence and metastasis in patients with NSCLC ( Cao et al, 2015 ); Wang et al found that low expression of ZBTB16 can promote the survival of NSCLC tumor cells and enhance their invasiveness ( Wang et al, 2013 ; Xiao et al, 2015 ). Our study revealed that these genes are heavily enriched in metabolism-related biological processes such as the poly-N-acetyllactosamine biosynthetic process, glycosphingolipid biosynthesis—lacto and neglect series process.…”
Section: Discussionmentioning
confidence: 99%
“…CDH3 has also been reported to be associated with prognosis in patients with colorectal adenocarcinoma and lung cancer. ( Xu et al, 2019 ; Hsiao et al, 2020 ). SELP is a member of the selectin family of cell adhesion molecules, and it mediates heterotypic aggregation of activated platelets to cancer cells and adhesion of cancer cells to stimulated endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the last three decades, several studies have reported the ability of CDH3 to accelerate the growth of multiple types of cancer, including lung (27), esophageal (9), colorectal (7) and breast cancer (28). A previous study has also suggested the involvement of CDH3 in promoting the motility of pancreatic cancer cells by activating Rho-family GTPases (8).…”
Section: Discussionmentioning
confidence: 99%